Identifying students’ anxiety in English speaking skill through group discussion - Thaib, Desiana; Hasan, Jhems Richard (Journal of English Teaching and Linguistic Issues (JETLI), 2022)
The objective of this research is to know the kinds of students' anxiety in speaking English and the factors that cause students' anxiety in speaking English. The method used in this research was a qualitative method. The results showed that all students felt anxious in speaking English in discussion, this affected the students' speaking performance in group discussion. In addition, factors that make students anxious, are pronunciation, grammar, vocabulary. This is implied by students' anxiety in speaking English skill through group discussion.